Uji Kesukaan Kue Muffin Berbahan Dasar Tepung Sorgum - Suesilowati Suesilowati; Rina Ekawati; Ratih Dwi Astuti; Pradnya Susanti (Politeknik Ganesha Medan, 2024)
This study aims to analyze consumer preference levels for muffins made from sorghum flour as an alternative to wheat flour. The study employs a quantitative approach using an experimental method involving 60 respondents. Data collection was conducted using a hedonic test to evaluate taste, aroma, color, texture, and appearance. The results indicate that sorghum-based muffins received a positive response, with the highest preference levels for appearance (4.3) and color (4.1), while texture received the lowest score (3.6). This study suggests that sorghum flour can be a viable alternative for healthier baked goods.